Amesiodendron tienlinense H. S. Lo (Sapindaceae Juss.) a new species for the flora of Vietnam - Tam, Ha Minh; Khoi, Nguyen Khac; Phuong, Vu Xuan (Academia Journal of Biology, 2014)
The genus Amesiodendron Hu (Sapindaceae Juss.) has 3 species, distributing in China and some countries of SE Asia (Vietnam, Laos, Thailand and Malayxia). According to Gagnepain (1950), Pham Hoang Ho (2000), Tran Kim Lien & Ha Minh Tam (2003)... in Vietnam, the genus Amesiodendron has 1 species (Amesiodendron chinense Hu). However, during the study of the specimen Nguyen Anh Tiep 596 collected in Hatinh province (Huongson) and the specimen Ha Tue 753 collected in Quangbinh province (Baren), we have identified that they are Amesiodendron tienlinense H. S. Lo, a new species for the flora of Vietnam. In this article, we introduced study results for the genus Amesiodendron Hu in Vietnam, including a key to the species in Vietnam and provided some infomations about morphology, ecology, distribution... of this species A. tienlinense H. S. Lo in the flora of Vietnam.